Appraisal and memory in Brazilian universities - Akaichi, Tatianne [UNESP]; Bizello, Maria Leandra [UNESP]; Troitino Rodriguez, Sonia Maria [UNESP] (Ibersid Network, 2018)
Documentary appraisal is a relevant function of the records management process, and consists of analyzing and establishing deadlines for the custody and destination of records (permanent custody or elimination) according to the primary or secondary values assigned to them. The present research presents the results obtained with archivists of Federal Institutions of Higher Education, seeking to verify in the appraisal process the importance of the archives to the memory. The research is of the exploratory type and the method of analysis used for its development is of quantitative and qualitative character. For the data collection, a questionnaire was applied, with open and closed questions, to 11 participants. With the obtained results it's emphasized the constant need for update the conserving periods of documents relative to the end-activity on the temporality table just as well it's enhanced the importance of the memory, as the records of activities developed by the institution and like an information source to produce knowledge, ensure rights, evidences and witness.
Keywords: Academic archives; Archival appraisal; Universities; Brazil